Racial and Ethnic Disparities in Maternal and Infant Outcomes Among Opioid-Exposed Mother–Infant Dyads in Massachusetts (2017–2019) - Peeler, Mary (Am J Public Health, 2020)
Objectives. To examine the extent to which differences in medication for opioid use disorder (MOUD) in pregnancy and infant neonatal opioid withdrawal syndrome (NOWS) outcomes are associated with maternal race/ethnicity. Methods. We performed a secondary analysis of a statewide quality improvement database of opioid-exposed deliveries from January 2017 to April 2019 from 24 hospitals in Massachusetts. We used multivariable mixed-effects logistic regression to model the association between maternal race/ethnicity (non-Hispanic White, non-Hispanic Black, or Hispanic) and prenatal receipt of MOUD, NOWS severity, early intervention referral, and biological parental custody at discharge. Results. Among 1710 deliveries to women with opioid use disorder, 89.3% (n = 1527) were non-Hispanic White. In adjusted models, non-Hispanic Black women (AOR = 0.34; 95% confidence interval [CI] = 0.18, 0.66) and Hispanic women (AOR = 0.43; 95% CI = 0.27, 0.68) were less likely to receive MOUD during pregnancy compared with non-Hispanic White women. We found no statistically significant associations between maternal race/ethnicity and infant outcomes. Conclusions. We identified significant racial/ethnic differences in MOUD prenatal receipt that persisted in adjusted models. Research should focus on the perspectives and treatment experiences of non-Hispanic Black and Hispanic women to ensure equitable care for all mother–infant dyads.